2019
DOI: 10.3201/eid2503.181213
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Influenza C Virus Infection among Hospitalized Patients, Cameroon

Abstract: We report 3 cases of influenza C virus in children hospitalized with severe acute respiratory infection in Cameroon. Two of these case-patients had grave clinical manifestations, but all 3 recovered. The lack of specific antiviral drugs for influenza C virus highlights the need to identify and describe cases involving this virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…A Japanese longitudinal study of 190 ICV isolates collected over seven years found that nearly all were <6 years old, with the highest rates of infection in children 1-2 years old [60]. Rates of detection of ICV in outpatient or hospitalized children with acute respiratory illness have ranged from 0.7-10% in studies from Australia, Canada, Cuba, India, Italy, Japan, Nigeria, Peru, Scotland, and Spain [1,12,20,61,63,68,70,[91][92][93][94][95][96][97][98][99][100][101][102]. Most of these studies found higher rates of ICV infection in younger children.…”
Section: Icv In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…A Japanese longitudinal study of 190 ICV isolates collected over seven years found that nearly all were <6 years old, with the highest rates of infection in children 1-2 years old [60]. Rates of detection of ICV in outpatient or hospitalized children with acute respiratory illness have ranged from 0.7-10% in studies from Australia, Canada, Cuba, India, Italy, Japan, Nigeria, Peru, Scotland, and Spain [1,12,20,61,63,68,70,[91][92][93][94][95][96][97][98][99][100][101][102]. Most of these studies found higher rates of ICV infection in younger children.…”
Section: Icv In Childrenmentioning
confidence: 99%
“…ICV infection is more commonly associated with hospitalization and lower respiratory disease in young children (Table 1). ICV-associated hospitalization occurs most often among children <3 years of age and cases of Intensive Care Unit admission among infants with prematurity and congenital heart disease have been described, as well as otherwise healthy young children [1,100,103]. Among children hospitalized for ICV infection, co-morbidity is reported in 58-80% of cases [1,103].…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Overall, as summarized in Atkinson et al ( 10 ), seropositivity has been reported to be between 57 and 100%, being lower in children and rising in adulthood. ICV has been considered a pathogen of low significance, as it generally causes mild disease or clinically inapparent infection ( 9 , 11 , 12 ), but in recent years it has become increasingly apparent that the virus can be associated with severe disease, notably in children with lower respiratory tract infections ( 12 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike influenza A and B viruses, influenza C viruses typically cause mild illness. However, in recent years, severe illness in children infected by influenza C virus has raised concerns over the lack of virus-specific therapeutics and vaccines ( 4 ). Recently discovered influenza D viruses were isolated from swine and bovines.…”
mentioning
confidence: 99%